Tingkat Persaingan pada Industri Tembakau dan Dampaknya terhadap Petani Tembakau (Studi Kasus Industri Tembakau Madura) - Bondan Satriawan (Universitas Negeri Surabaya, 2018)
This study tries to explore the degree of competition in tobacco Industry in Madura. By doing so, this study examines the competition in all markets of the distributional levels of Maduras tobacco, from farmer to tobaccos final user. In addition, for every market of the distributional level, the discussion is focused on the competition among the sellers themselves, the buyers themselves and also the consequences for the sellers and the buyers in terms of price, strategic behavior and profit. Linear œStructure-Conduct-Performance (S-C-P) model is being used as the main framework in this study. Additionally, this study uses primary and secondary data. Furthermore, this study shows that in the upstream industry of tobacco, the degree of competition is almost perfect, and as it gets closer to the downstream industry of tobacco the degree of competition is close to monopoly. Hence, the closer a firm to the upstream industry of tobacco, the profit is less, and as it gets closer to the downstream industry of tobacco, the profit is much higher, as well as its monopoly or market power. In turn, this condition is negatively impacting the tobacco farmer welfare as the upstream firm.